A Survey on Encryption and Improved Virtualization Security Techniques for Cloud Infrastructure (Global Journal of Computer Science and Technology, 2014)
Cloud Computing is one of the latest developments in the IT industry which offers on-demand services without requiring to create an IT infrastructure. It provides scalability, high performance and relatively low cost feasible solution for organizations. Despite of all its advantages, security is still a critical challenge in cloud computing paradigm. This paper presents a survey on some possible techniques used for encrypting user data and also providing techniques used in improving virtualization security for the cloud infrastructure.
Keywords: cloud computing; scalability; security; virtualization